Training Using Central Resistance On The Development of Biomechanical Variables For Performance Phases and 100m Running Achievement - Abdul Kareem, Sareeh; Bader, Yousif (Journal of Physical Education, 2019)
The research aimed at designing special training using treadmill adding center of gravity resistance to identify the effect of biomechanical variables for 100m running performance level.  The researchers' hypothesized differences between pre and posttests in some motor biomechanical variables of 100m running phases. The researchers used the experimental method on subjects from the national center for gifted. Strength and muscular ability was measured mechanically using dynavolt for phases of running as well as measuring number and strides using videotaping. The training program was applied for ten weeks with three training sessions per week. The researchers concluded that using training aids develop strength and motor fluency.